MECHANISM OF INITIATION AND REGENERATION CONVECTIVE CELL IN BANDUNG BASIN (CASE STUDY: FEBRUARY - MARCH 2019) - Maulana Firdaus, Irfans
In this study, the mechanism of initiation and regeneration convective cell in the Bandung Basin are investigated using a numerical model. Numerical model simulations were carried out using case studies in the February - March 2019 based on Cumulative Distribution Function (CDF) and Regeneration Index (RegI). The mechanism of convective cell initiation is described as follows: (i) Upslope wind is formed by solar heating effect and flows to the north and south of the basin, carrying water vapor from the bottom of the basin. (ii) Low-level convergence is formed in the mountain peak region due to the convergence of winds from bottom of the basin and outside of the basin. (iii) Convective initiation is formed due to the updraft by generated from low-level convergence, causing unstable atmosphere. While the mechanism of convective cells regeneration is described as follows: (i) Convective systems which develop in mountains produce rain and generate cold pools on the surface. The cold pool will fall down the slopes and convective activity from the mountainous will continue to the bottom of basin. (ii) The outflow from this convective system causes the cold pool to extend to west-east. (iii) The cold pool will collide with warmer air from the opposite direction, resulting an updraft at the cold pool leading edge (CPLE) and convective will re-initiate (convective regeneration) in the Bandung Basin, with the new convective system tend to move eastward.